Examining How Islamic Coping Reduces Internet Misuse through Emotional Self-Regulation - Hafizah, Nurul; Uyun, Qurotul (Journal An-Nafs: Kajian Penelitian Psikologi, 2023)
Problematic internet use (PIU) has emerged as a serious psychological concern, particularly among youth during the COVID-19 pandemic. While prior studies have explored emotional and behavioral factors contributing to PIU, limited research has examined how culturally grounded religious coping strategies influence these patterns. This study offers a novel contribution by investigating the mediating role of emotion regulation difficulties in the relationship between Islamic religious coping and PIU among Muslim undergraduate students in Indonesia. A quantitative approach was applied to a sample of 304 participants using the Iranian Religious Coping Scale (IRCOPE), Difficulties in Emotion Regulation Scale-18 (DERS-18), and Generalized Problematic Internet Use Scale 2 (GPIUS-2), all adapted into Indonesian. Path analysis revealed that Islamic religious coping significantly reduced emotion regulation difficulties, which in turn were positively associated with PIU. Notably, religious coping did not directly impact PIU but exerted an indirect effect through emotional regulation. These findings underscore the relevance of culturally specific, faith-based strategies in managing excessive internet use and contribute to the broader integration of Islamic psychological constructs within contemporary behavioral research. This study advances the field by modeling a culturally contextualized pathway from religiosity to digital behavior, with implications for culturally informed interventions.